Early prenatal detection of anterior uterine sacculation resulting from previous cesarean sections. Issue 2 (13th November 2019) - Traisrisilp, Kuntharee; Bootchaingam, Phenphan; Sreshthaputra, Opas; Tongsong, Theera
Abstract: Anterior uterine sacculation was diagnosed at 15 weeks of gestation in a woman with two previous cesarean sections, based on hourglass appearance of two distinct uterine segments, namely the empty upper segment and the large thinned wall lower segment containing a fetus with posteriorly attached placenta. The pregnancy developed through the bulging weakened anterior wall instead of growing toward the upper segment. Urgent hysterectomy was performed. The operative and pathological findings confirmed the prenatal ultrasound findings. This is the first report of prenatal diagnosis of sacculation due to cesarean section, which prevented the catastrophic event of uterine rupture.